Comparison to the Iron Level on the well water and PDAM water sample using ICP-OES Spectrophotometer - Fadhilah, Alya Melanisya; Nurhidayanti; Juraijin, Denny (Universitas PGRI Palembang, 2023)
Iron (Fe) is one of the elements that can be found in almost every place on earth, in all geological levels, and in all water bodies. In general, the iron in the water can be dissolved. The content of Fe ions in drilled well water can range between 5-7 mg/L. ICP-OES spectrophotometry is a type of ICP that utilizes plasma as a source of atomization and excitation. The purpose of this research is to determine the difference in Fe content between well water samples and PDAM water samples in the Pemulutan sub-district using the ICP-OES spectrophotometer. The type of research used was cross-sectional. The population in this study was well-watered and PDAM-watered in Pemulutan District. The sampling technique in this study was simply random. The place of this research was in the Palembang Health Laboratory Center. The results showed that the average difference in the examination of Fe levels in well water samples and PDAM water using the sda was 0.13198 mg/L for well water and 0.00445 mg/L for PDAM water. The conclusions were that PDAM water is safer to use for sanitation activities or consumption purposes than well water. The iron (Fe) content in well water is higher than the iron (Fe) content in PDAM water.